Does Sensory Integration Affect the Clinical Picture of Autism Spectrum Disorder? - Novaković, Neda B; Pejović Milovančević, Milica M (Medicinski časopis, 2020)
Background: The latest classification system of American Psychiatric Association (APA) DSM-5 includes sensory problems as one of the diagnostic criteria for autism spectrum disorder (ASD). Objective: To determine the relationship between the severity degree of autism spectrum disorder and sensory integration by sensory domains. Method: The sample involved 40 participants with ASD, both sexes, aged 15-35. The study examined the relationship of ASD severity degree and sensory integration based on estimation of seven sensory modalities. Measures: The scale determining the degree of autistic disorder (Childhood Autism Raising Scale – CARS) completed by the therapists/special educators. The scale estimating sensory integration dysfunction (The Scale Estimating Sensory Integration Dysfunction in order to determine hyper – or hyposensitivity) completed by the parents and therapists/special educators. Results: Except for the oral-gustatory sense in this research no correlation was found between the severity degree of symptoms of ASD and sensory integration by sensory domains, according to the therapist estimations. The absence of the correlation of sensory modalities and disorder severity were confirmed in other studies. The relationship across the sensory domains was found.  Conclusion: Sensory integration disorder is a general issue and is present in ASD population in all categories of disorder severity.  It is important, as ASD population is heterogenous, to observe sensory domains separately in order to determine individual specificities in ASD population, and to administer all assessment categories in each sensory domain. Keywords: Severity of autism spectrum disorder, Sensory integration disorder, Sensory domains